The Level of Knowledge of Jatimulya Bekasi Village Residents on the Use of Vitamin C during the Covid 19 Pandemic and According to Islamic Overview - Rana Alifiah Nur Syarifah; Dharma Permana; Andri Gunawan (Junior Medical Journal, 2023)
Coronavirus disease 2019 (COVID-19) is a respiratory tract infection disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The percaution to avoid COVID-19 virus is to take vitamin C to boost the body's immune system. This research is a correlative-descriptive studies, with cross-sectional method in Kelurahan Jatimulya Bekasi in RT 001 and RT 002 RW 013 for residents aged 17-55 years old. Using simple-random sampling method, 123 residents who consumed vitamin C used as respondents with digital questionnaire. The answers from the questionnaire used to group respondents according to their three level categories knowledge of satisfactory, intermediate and low. Descriptive-analysis was conducted to see the characteristics. Data analysis was also carried out by making frequency tables between the level of knowledge in correlation with age, education, and occupation. Based on the analysis of the questionnaire results, it was found that majority of 65 respondents (52.8%) had satisfactory knowledge regarding the use of vitamin C, with characteristics age 17 – 25 years old, had non-medical tertiary education, and work in private sector. Research using the Chi-Square statistical test found that there was a significant correlation between age (p=0,002) with the knowledge of the use of vitamin C. The good knowledge of respondents is received information about the use of vitamin C from health workers, electronic media, packaging Information-content and educational institutions. In Islam overview, gaining knowledge is an obligation as mentioned in Q.S. Ali-Imran (3):190.